The dark side of religious individualism: A Marcusian exploration. (August 2019) - Spickard, James V
Sociologists of religion have recently focused on the growth of religious individualism in Western societies. Whether seen as a new religious trend or as a cultural correlate to the general weakening of civic organizations in the contemporary era, it is often presented as the growing tendency in religious life. It is also frequently presented in a positive light. This article explores a different alternative. Based on the work of Herbert Marcuse, it asks whether religious individualism heightens or undercuts the possibility of opposition to the status quo. Marcuse's underlying argument implies that when religion becomes a lifestyle choice, it becomes just another consumer good—one that encourages a one-dimensional "happy consciousness" that lacks the depth to support true social critique. In this view, religious individualism undercuts human emancipation.